Olfactory reference disorder—a review - Savitha Soman; Rajesh Nair (Middle East Current Psychiatry, 2023)
Abstract Olfactory Reference Disorder (ORD) is a known clinical entity for several decades; however, it is only in ICD 11 that it has found its niche. Long considered a delusional disorder, it is currently classified as an obsessive–compulsive (OC) spectrum disorder. ORD is characterised by an erroneous conviction that the body is emitting an unpleasant smell. Patients harbour referential thinking, practise rituals to eliminate or mask the perceived odour, and avoid social interactions. While the conviction can be at a delusional level in some patients, the preoccupation has an obsessive quality in others. The level of insight can be varied. Patients present to mental health settings after traversing a long pathway of care comprising of various specialists. Medical and psychiatric conditions which can present with ORD-like symptoms need to be ruled out. Establishing a therapeutic alliance is the first step in management. There are no randomised controlled trials comparing treatment options in ORD. Antidepressants, antipsychotics, and their combinations have been used with varying degrees of success, in addition to psychotherapy and electroconvulsive therapy. Data on prognosis is limited.